Feeding with Artificial Feed on Sand Goby, Oxyeleotris marmorata (Blkr.), Fry - Sudrajat, Agus Oman; Effendi, Irzal (Indonesian Society of Scientific Aquaculture (ISSA), 2002)
ABSTRACTThe influence of feed shape and protein resource of artificial feed on the growth and survival rate of sand goby, Oxyeleotris marmorata (Blkr.), fry were evaluated in this experiment. This experiment purposed to determine growth rate, survival rate, feeding efficiency, protein retention, lypid retention and look for the suitable artificial feed for sand goby. This experiment was carried out at the Laboratory of Aquaculture System and Technology, Department of Aquaculture, Faculty of Fisheries and Marine Sciences, Bogor Agricultural University in Bogor. Factorial design was used in this experiment with two factors: feed shape and protein resource. There were two kinds of feed shape: dry pellet and moist pellet. Protein resource consisted: fish, squid, and shrimp. The sand goby juveniles were kept in aquarium 60x30x40 cm was filled 40 litre of aerated. The fish were fed of 7% (dry weight based) of body weight in three time of feeding (10:00, 14:00, 18:00 WIB), 30, 30, 40% total feed/day respectively. The amount of feed was adjusted every 7 days with sampling. The juveniles feeding with shrimp-moist showed better survival rate, growth rate, feeding efficiency, protein retention, lypid retention than those fed shrimp-dry, squid-dry, squid-moist, fish-dry, and fish-moist. Dry pellet and moist pellet can be used for sand goby feeding. The artificial feed for sand goby juvenile suggested contain attractant and had highly water stability. Shrimp and squid can be used as main protein resources in artificial feed for sand goby. Key Word : Feeding, artificial feed, sand goby, Oxyeleotris marmorata, fry. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh bentuk pakan dan sumber protein dari pakan buatan terhadap pertumbuhan dan kelangsungan hidup ikan betutu, Oxyeleotris marmorata (Blkr.). Rancangan faktorial dengan 2 faktor, bentuk pakan (pelet basah dan pelet kering) dan sumber protein (ikan, cumi dan udang) digunakan dalam penelitian ini. Ikan diberi pakan 7% bobot badan basah yang diberikan dalam 3 kali per hari. Ikan yang diberi pakan dengan kombinasi bentuk pelet basah dan sumber protein udang (pelet basah-udang) menunjukkan kelangsungan hidup, pertumbuhan, efisiensi pemberian pakan dan retensi protein terbaik dari perlakuan lainnya. Udang dan cumi dapat digunakan sebagai sumber protein utama dalam pakan buatan untuk ikan betutu. Pakan buatan untuk benih ikan betutu disarankan mengandung atraktan dan memiliki stabilitas dalam air yang tinggi.Kata kunci : Pemberian pakan, pakan buatan, ikan betutu, Oxyeleotris marmorata, benih.